MACROECONOMIC INDICATORS AND COMMERCIAL BANKS’ RISK ASSETS CREATION IN NIGERIA - Mike Ozemhoka, Asekome; Abraham Oni, Agbonkhese (European Scientific Journal, ESJ, 2014)
The study attempts to empirically determine the effects of macroeconomic indicators/variables on risk assets creation in Nigeria from 1981 to 2011. The econometric technique explored is the Ordinary Least Square (OLS) method. From the empirical result, all the variables of interest were in tandem with theoretical expectations except gross domestic product. This may be attributable to inconsistencies in macroeconomic policies of government or policy makers. Similarly, considering the t-values, all the variables were statistically significant as well except capacity utilization of industries. This may not be unconnected with capacity under utilization that has bedeviled the manufacturing industry over the years. One of the policy recommendations is the need for banks to reduce their lending rate. High lending rate has not been helpful to the real sectors as it tends to discourage credit to the productive sectors of the economy. Also, macroeconomic policies that promote low inflation, low interest rate, favourable and stable exchange rate and enhance capacity utilization of industries should be formulated as this will boost credit expansion, increase returns and profitability of commercial banks and this will in turn trickle down on the economy positively.